Why Do Minority Men Earn Less? A Study of Wage Differentials among the Highly Educated - Black, Dan; Haviland, Amelia; Sanders, Seth; Taylor, Lowell (The Review of Economics and Statistics, 2006)
We estimate wage gaps using nonparametric matching methods and detailed measures of field of study for university graduates. We find a modest portion of the wage gap is the consequence of measurement error in the Census education measure. For Hispanic and Asian men, the remaining gap is attributable to premarket factors—primarily differences in formal education and English language proficiency. For black men, only about one-quarter of the wage gap is explained by these same factors. For a subsample of black men born outside the South to parents with some college education, these factors do account for the entire wage gap.